2016
DOI: 10.1080/13668803.2015.1134127
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory support in Slovenian and Dutch organizations: a contextualizing approach

Abstract: This paper builds on the influential work of Suzan Lewis examining how employees' work-life experiences are shaped by different layers of context. Our approach is therefore a comparative one using data from four organizational contexts in two countries, the Netherlands and Slovenia. Within each organization, we examine the role of different types of supervisory support (specific family support and general support) and the quality of the relationship between supervisor and subordinate (LMX) in work-to-family co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
1
23
0
2
Order By: Relevance
“…They may also feel less pressured to invest themselves completely in their work role at the expense of their family. Perceived managerial work-life support leads to less work–family conflict as well, as it is easier to discuss conflicting issues and more likely to receive empathy from a supervisor who is supportive of work-life issues, instead of one who views these as a private matter (Den Dulk et al 2016 ; Major et al 2008 ). We thus argue that a work–family supportive context may also be influential to what extent working from home causes work–family conflict.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also feel less pressured to invest themselves completely in their work role at the expense of their family. Perceived managerial work-life support leads to less work–family conflict as well, as it is easier to discuss conflicting issues and more likely to receive empathy from a supervisor who is supportive of work-life issues, instead of one who views these as a private matter (Den Dulk et al 2016 ; Major et al 2008 ). We thus argue that a work–family supportive context may also be influential to what extent working from home causes work–family conflict.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…There is evidence that a supportive organizational context is important to alleviate work-life conflict (cf. Den Dulk et al 2016 ; Chung, in this issue), but a number of scholars indicated that there is void of research studying how cultural-normative organizational contexts are of influence on family-friendly policies and employee outcomes (Allen et al 2015b ; Kossek et al 2006 ; Den Dulk et al 2016 ). The present paper fills this gap by providing insight in how the organizational context shapes the impact of working from home on work–family conflict.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider employee and managerial discourses to gain insight into why, even in the case of strong national and cultural work–life support at the macro level, employees sometimes lack the agency, within the local organizational context, to fully use existing policies ( Den Dulk, Peper, Kanjuo Mrĉla, & Ignjatović, 2016 ). Following Watson (2001) , discourses refer to “connected sets of statements, concepts, terms and expressions which constitute a way of talking and writing about a particular issue, thus framing the way people understand and act with respect to that issue” (p. 113).…”
mentioning
confidence: 99%
“…Allen, culture and family-supportive supervision were both related to work-home inter ference in all countries (Beham, Drobnic, & Prag, 2014). FSS has also shown to be negatively related to work-family conflict and positively related to both work-family enrichment and satisfaction with work-family balance in a Slovenian hospital, as well as positively related to work-family enrichment in a Dutch university and work-family balance satisfaction at a Dutch consultancy firm (Den Dulk, Peper, Mrcela, & Ignjatovic, 2016). The negative relationship between FSS and work-family conflict has also been demonstrated in samples in Iran (Farhadi, Sharifian, Feili, & Shokrpour, 2013), New Zealand (O'Driscoll, Poelmans, Spector, Kalliath, Allen, Cooper, & Sanchez, 2003), as well as South American countries like Peru (Agarwala et al, 2014).…”
Section: Relationships Between Fss and Key Work-family Constructsmentioning
confidence: 92%
“…In the United States, effects of FSS have been found for both managerial and professional-level employees (e.g., , as well as low-wage workers (e.g., Griggs, Casper, & Eby, 2013;Hammer et al, 2011;Muse & Pichler, 2011). A global review of family-supportive supervision research, however, reveals that studies appear to largely be conducted on managerial and professional-level employees outside of the United States (e.g., Agarwala et al, 2014;Den Dulk, Peper, Mrcela, & Ignjatovic, 2016;O'Driscoll, Poelmans, Spector, Kalliath, Allen, Cooper, & Sanchez, 2003), while some have a mix of employee levels (e.g., Beham, Drobnic, & Prag, 2014), or where job level is not noted (e.g., Allen et al, 2014). An exception would be a sample of nurses and nurse assistants in Iran where family-supportive supervision was found to negatively predict work-family conflict and job stress (Farhadi et al, 2013).…”
Section: Future Cross-national Research On Often Overlooked Moderatormentioning
confidence: 99%